2018
DOI: 10.1111/jre.12572
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐543 functions as an osteogenesis promoter in human periodontal ligament‐derived stem cells by inhibiting transducer of ERBB2, 2

Abstract: Background and Objective Previous research has indicated that altered expression of microRNAs (miRNAs) is in connection with osteogenesis of human periodontal ligament‐derived stem cells (hPDLSCs). We investigated the mechanisms by which miR‐543 promotes osteogenic differentiation of hPDLSCs. Material and Methods First, the expression of miR‐543 in hPDLSCs cultured with or without an osteogenic inductive cocktail was explored. Then, the function of miR‐543 during osteogenesis of hPDLSCs was investigated by ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Singlecell suspensions were inoculated into six-well plates at a density of 1 × 10 4 cells/well. Limited dilution techniques were used to obtain colonies of single-cell origin [24].…”
Section: Methodsmentioning
confidence: 99%
“…Singlecell suspensions were inoculated into six-well plates at a density of 1 × 10 4 cells/well. Limited dilution techniques were used to obtain colonies of single-cell origin [24].…”
Section: Methodsmentioning
confidence: 99%
“…LncRNA LEF1-AS1 Glioblastoma Bing et al (2014) LncRNA THUMPD3-AS1 Non-small-cell lung cancer C. C. Wang et al (2018) LncRNA SNHG10 Non-small-cell lung cancer P. Chen et al (2017) Linc-PINT Non-small-cell lung cancer Clevers (2006) Esophageal cancer Dang et al (2017) LncRNA HCG11 Prostate cancer Du et al (2017) LncRNA PCAT6 Cervical cancer Evert et al (2018) LncRNA PVT1 Rheumatoid arthritis Fan et al (2016) LncRNA SNHG7 Diabetic retinopathy Fuentes-Mattei et al 2020LncRNA RNF7 Cardiac fibrosis Ge et al (2018) LncRNA XIST a Atherosclerosis Guglielmelli et al (2015)…”
Section: Lncrnamentioning
confidence: 99%
“…RNA polymerase III Dicer processes pre-miRNAs into mature miRNAs [41]. Studies have shown that mature miRNAs bind with the 3′-UTR of target mRNA completely or incompletely, which influences the stability of mRNAs or inhibits their translation and eventually downregulates protein expression [42][43][44]. In addition to this main mechanism, other unconventional mechanisms are gradually being explored ( Fig.…”
Section: Micrornas Analysis During Odontogenesismentioning
confidence: 99%